TO SYNTHESIZE, CHARACTERIZATION AND PHARMACOLOGICAL EVALUATION OF NOVEL SUBSTITUTED ISATIN DERIVATIVES - D B Joshi (Journal of Biomedical and Pharmaceutical Research, 2020)
Series of novel Schiff bases of Isatin the equimolar amines and 5-Dicrboxymethyl (R=COO2Me) substituted isatins (1 mmol of each) were added to 96% w/w ethanol (20 mL) containing 8 drops of glacial acetic acid. The mixture was heated under reflux for 5 h and then cooled to room temperature. The resulting solid was collected by filtration, washed with cold ethanol and dried in open air. The derivatives thus prepared had sufficient analytical purity. anticonvulsant activity performed by method as Animals were weighed and numbered. Mice were divided into 7 groups of six animals each. Group 1 served as control which was treated with vehicle (2% v/v Tween 80), group 2 was treated with standard drug phenytoin (25 mg/kg, i.p.) and groups 3– 7 were treated with newly synthesized oxadiazole derivatives (25 mg/kg, i. p.). One hour after injection, the animals were subjected to electro shock through ear electrodes of 80 mA for 0.2 sec by electroconvulsiometer AND ANTI-inflammatory activity measured by Weigh the animals and number them. Mark the animals with picric acid for individual animal identification. Divide rats into 5 groups of 6 rats each. Note the initial paw volume of each rat by dipping just beyond tibio-tarsal junction by mercury displacement method. The pharmacological screening of the synthesized compounds showed anti convulsant activity ranging from 56.2 % to 76.3 % inhibition of epileptic seizures in mice, where as the standard drug Phenytoin showed 83.95 % inhibition of epileptic seizures in mice. The compound iiih4 from each group was found to be nearly potent to Phenytoin which is used as standard drug. Anti-inflammatory activity ranging from 31.09 to 63.11 % inhibition of rat paw edema volume after 3 hours, whereas the standard drug Indomethacin showed 62.06 % inhibition of rat paw edema volume after 4 hours. The compound iiih3 was found to be nearly more potent then indomethacin which is used as standard drug Keywords: Isatin; Schiff bases; Anti convulsant activity; Anti-inflammatory activity; Isatin.